Analisis Rasio Profitabilitas Dan Likuiditas Terhadap Kinerja Keuangan Pada Bank BRI Unit Manarng Cabang Pinrang - Nurhalima Nurhalima; Milka Pasulu; Andi Herman Tellu (Universitas Katolik Widya Karya Malang, 2024)
The aim of this research was to determine the financial performance of Bank BRI Manarang Unit, Pinrang Branch. The research method used is quantitative research. By using Profitability Ratios and Liquidity Ratios to measure Financial Performance for three years. The research results show that financial performance in terms of profitability/profit aspects is in good condition, where profits generated from assets and investments in the last three years show good condition. Meanwhile, the ability to fulfill short-term obligations/liquidity shows good ability.